Consequences of interplant trait variation for canopy light absorption and photosynthesis - van der Meer, Maarten; Lee, Hyeran; de Visser, Pieter H. B.; Heuvelink, Ep; Marcelis, Leo F. M. (Frontiers in Plant Science, 2023)
Plant to plant variation (interplant variation) may play an important role in determining individual plant and whole canopy performance, where interplant variation in architecture and photosynthesis traits have direct effects on light absorption and photosynthesis. We aimed to quantify the importance of observed interplant variation on both whole-plant and canopy light absorption and photosynthesis. Plant architecture was measured in two experiments with fruiting tomato crops (Solanum lycopersicum) grown in glasshouses in the Netherlands, in week 16 (Exp. 1) or 19 (Exp. 2) after transplanting. Experiment 1 included four cultivars grown under three supplementary lighting treatments and Experiment 2 included two different row orientations. Measured interplant variation of the architectural traits internode length, leaf area, petiole angle and leaflet angle, as well as literature data on interplant variation of photosynthesis traits alpha, Jmax28 and Vcmax28 were incorporated in a static functional–structural plant model (FSPM). The FSPM was used to analyze light absorption and net photosynthesis of whole plants in response to phytomer level interplant variation in architectural and photosynthesis traits. Introducing interplant variation in architecture and photosynthesis traits in a functional structural plant model did - depending on the trait - not or negatively affect canopy light absorption and net photosynthesis compared to the reference model without interplant variation. Introducing interplant variation of architectural and photosynthesis traits in FSPM results in more realistic simulation of variation of plants within a canopy. Furthermore, it can improve the accuracy of simulation of canopy light interception and photosynthesis, though these effects at canopy level are relatively small (<4% for light absorption and <7% for net photosynthesis).